Effectiveness Of Toothbrush Storage Education In The New Normal Era Of The Covid-19 Pandemic At TP-PKK Lubeg Padang - Monica Wihanda Kurnia; Dedi Sumantri; Adi Sri Nengsih (Jurnal Kesehatan Gigi, 2022)
Problem statement. The education of toothbrush storage needs to be carried out, so people can understand the importance of proper toothbrush storage. This is because toothbrushes can be a breeding ground for microorganisms, including the Covid-19 virus. The purpose of this study was to determine the effectiveness of toothbrush storage education during the new normal era of the COVID-19 pandemic at TP-PKK Lubeg Padang. Method. This research was conducted using a pre-test and post-test questionnaire method with educational material intervention regarding the proper storage of toothbrushes. Scientific finding results. The given intervention shows low effectiveness. Short conclusion. Toothbrush storage education for TP-PKK Lubeg women is less effective if done online.